2022
DOI: 10.1080/19490976.2022.2091369
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal accumulation of microbiota-produced succinate caused by loss of microRNAs leads to diarrhea in weanling piglets

Abstract: Diarrheal disease is a common health problem with complex causality. Although diarrhea is accompanied by disturbances in microbial diversity, how gut microbes are involved in the occurrence of diarrhea remains largely unknown. Here, using a pig model of post-weaning stress-induced diarrhea, we aim to elucidate and enrich the mechanistic basis of diarrhea. We found significant alterations in fecal microbiome, their metabolites, and microRNAs levels in piglets with diarrhea. Specifically, loss of ssc-miRNA-425-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Fixed liver samples were paraffin embedded and sectioned into 8-μm thick sections; then, the samples were either subjected to H&E (hematoxylin–eosin) staining for histological observation or Oil Red O staining for the determination of lipid content as previously described ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fixed liver samples were paraffin embedded and sectioned into 8-μm thick sections; then, the samples were either subjected to H&E (hematoxylin–eosin) staining for histological observation or Oil Red O staining for the determination of lipid content as previously described ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…The db/db diabetic mice were first orally gavaged with 0.2 mg ampicillin, 0.1 mg vancomycin, 0.2 mg neomycin, 0.2 mg streptomycin and 0.2 mg metronidazole dissolved in 0.2 mL PBS for 7 consecutive days as previously described ( Zhou X. et al, 2022 ). Then, the db/db mice were gavaged with 5 mg freshly collected feces suspended in 0.2 mL PBS, either from mice in the db/db group or from those in the SeSer group.…”
Section: Methodsmentioning
confidence: 99%
“…The role of an intestinal gluconeogenic substrate in maintaining intestinal energy metabolism has also been studied ( De Vadder et al., 2016 ). On the other hand, numerous studies point to succinate as a danger signal that can aggravate intestinal mucosal damage and promote the development of inflammation ( Fremder et al., 2021 ; Zhou et al., 2022b ). Therefore, we can speculate that succinate may plays its role as a signal molecule depending on the specific cell types or disease states.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have demonstrated the effect of short-chain fatty acids on the progression of intestinal health in patients with NEC and demonstrated that they show predictive value for NEC development (Roy et al, 2018;Sun et al, 2021;Liu et al, 2022a). Succinate, widely regarded as an intermediate molecule of the mitochondrial tricarboxylic acid cycle, has recently emerged as a key player in maintaining intestinal homeostasis, intestinal energy metabolism, and immune regulation (De Vadder et al, 2016;Banerjee et al, 2020;Zhou et al, 2022b). A study pointed out that succinate can alter bacterial virulence while increasing bacterial invasion in inflammatory bowel disease (Zaidi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation